Pengaruh jenis pemanis terhadap pH dan aktivitas antioksidan sirup pucuk mangga (Mangifera indica) - Risda Arba Ulfa; Aep Saepuloh; Tri Cahyanto; Adisty Virakawugi Darniwa; Ayuni Adawiyah (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2022)
Mango is a type of plant that is common in tropical climates, including Indonesia. The pharmacological effects of the mango are contained in almost all parts of the plant, including the mango shoots. The mango shoots are known to benefit as antibacterial, anti-inflammatory, antitumor, antioxidant, and anti-microbial. This encourages many parties to make functional food preparations from mango shoots without destroying the nutrient contains. This study aims to evaluated the effect of adding different types of sweeteners on the quality of mango shoot syrup. This study used a completely randomized design (CRD) with three treatment groups consisting of control (T0), Stevia (T1), and Sugar (T2). Parameters observed included pH value, phytochemical screening, and antioxidant activity. The results showed that the pH values of all treatments ranged from 4.48-4.50 and were not significantly different (P=0.661). In the phytochemical screening test, all treatments showed positive results containing alkaloids, flavonoids, saponins, and tannins. Furthermore, based on the percentage value of the antioxidant activity, significant results were obtained (P = 0.000) with the IC50 value in the stevia treatment (8.98) which was smaller than sugar (19.14).The addition of stevia sweetener has a minimum effect in changing the nutritional content of mango shoot syrup based on the value of the antioxidant activity.